Pengaruh Pengetahuan Pajak, Sosialisasi, Digitalisasi, terhadap Kepatuhan Pajak dengan Moderasi PP Nomor 58 Tahun 2023 - Erika Rahma Setiyani; Ahmad Dahlan; Kohar Adi Setia (FKDP (Forum Komunikasi Dosen Peneliti), 2026)
This study aims to analyze the effects of tax knowledge, tax socialization programs, and tax system digitalization on taxpayer compliance, with Government Regulation (PP) Number 58 of 2023 as a moderating. This study employed a quantitative approach using a survey method. The population consisted of 60 lecturers at Universitas Tulungagung. Data were collected through questionnaires and analyzed using SEM–Partial Least Squares. The findings indicate that tax knowledge and perceptions of tax system digitalization have a positive and significant effect on taxpayer compliance, whereas participation in tax socialization programs has no significant effect. The utilization of PP Number 58 of 2023 was found to moderate the relationships among the variables by weakening the effect of tax knowledge on taxpayer compliance, strengthening the effect of participation in tax socialization on taxpayer compliance, and weakening the effect of perceptions of tax system digitalization on taxpayer compliance, although the latter moderating effect was not statistically significant. Furthermore, the utilization of PP Number 58 of 2023 has a positive and significant direct effect on taxpayer compliance. These findings suggest that tax policies providing administrative simplification and procedural convenience can enhance taxpayer compliance while altering the influence of behavioral factors on individual taxpayer compliance.